Formation mechanism and application potential of carbon dots synthesized from palm kernel shell via microwave assisted method - Balakrishnan, T. (KeAi Publishing Communications Ltd., 2022)
The present study systematically investigated the influence of synthesis conditions (duration, reaction medium, and doping concentration) and formation mechanism of carbon dots (CDs) derived from low-cost and abundant biomass palm kernel shell (PKS). Surprisingly, the dopant (urea) did not enhance the photoluminescence of CDs as expected, which could be attributed to the low reactivity between the dopant and PKS macromolecules. Variation of synthesis duration from 30 to 120 s clearly indicated the formation mechanism of CDs, involving the stages of dehydration, carbonization, and nucleation. The CDs with the highest photoluminescent intensity and quantum yield was obtained at synthesis duration of 90 s, aligned well with the perfect spherical shape of CDs and the synergistic effects of both surface and carbogenic core conditions. Understanding the formation mechanism could be used to optimize the synthesis of CDs, and hence linked to quantum yield and fluorescent intensity. In terms of application potential, the CDs illuminated well as fluorescent ink and in bacteria cells imaging. The potential of CDs as sensing material has also been proven with the quenching of fluorescence in the presence of metal ions. The linear range for detection of Cu2+ ions was 0.1â0.5 mM with a detection limit as low as 0.05 mM. This signifies the potential of CDs fabricated from PKS as a low-cost and easily available material for Cu2+ ions detection in aqueous solution. The CDs possessed reasonable photo stability as indicated by its consistent fluorescence level even after exposure to UV radiation for a prolonged period of 180 minutes. Overall, a simple, straightforward, and fast method is developed to synthesis strong blue emissive CDs from green PKS that are potentially suitable for Cu2+ ions sensing in real application. Â© 2022